Teachers Difficulty and Coping Strategies in Physics - Navos, Donalie B.; Ordoña, Merlie B.; Llorente, Jean M.; Camarao, Michael Kennedy G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study investigates the difficulties encountered by physics educators and their coping strategies. Physics teaching presents various challenges such as addressing student misconceptions and integrating real-life examples. Understanding these challenges is crucial for developing effective coping strategies and enhancing physics education quality. Research suggests that addressing these challenges can improve teacher competency and student engagement. Investigating teachers' difficulties and coping strategies is vital for advancing the field and achieving successful learning outcomes. Ten teachers from public and private schools in Sultan Kudarat province participated in the study and were selected through purposive sampling. Data were collected using semi-structured interviews and focus group discussions with careful adherence to ethical standards. Results revealed challenges including teacher competency, students' weak mathematical foundations, and low retention. Coping mechanisms involved instructional preparation, peer mentoring, and real-life application of physics concepts. Despite the hurdles, educators exhibit resilience through various coping mechanisms, emphasizing the importance of targeted interventions and support systems. By fostering collaboration, emphasizing real-world applications, and providing ongoing professional development, educators can enhance the quality of physics education and facilitate meaningful learning experiences for students.